2016
DOI: 10.1371/journal.pone.0155496
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh Cognitive and Behavioural ALS Screen in a Chinese Amyotrophic Lateral Sclerosis Population

Abstract: ObjectiveThe existing screening batteries assessing multiple neuropsychological functions are not specific to amyotrophic lateral sclerosis (ALS) patients and are limited to their physical dysfunctions, whereas category cognitive tests are too time-consuming to assess all the domains. The Edinburgh Cognitive and Behavioural ALS Screen (ECAS) was recently developed as a fast and easy cognitive screening tool specifically designed for patients. The purpose of the study was to validate the effectiveness of the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 36 publications
9
48
3
Order By: Relevance
“…based on ACE-III and FAB, respectively This is similar to the rates of cognitive impairment found in previous studies [13,16] ( Table 2). The prevalence of behavioral impairment in our cohort is also just over 30% and approximately 40% based on ALS-FTD-Q and MiND-B.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…based on ACE-III and FAB, respectively This is similar to the rates of cognitive impairment found in previous studies [13,16] ( Table 2). The prevalence of behavioral impairment in our cohort is also just over 30% and approximately 40% based on ALS-FTD-Q and MiND-B.…”
Section: Discussionsupporting
confidence: 90%
“…Age and lower levels of education have been observed in several previous ALS studies as risk factors for cognitive impairment [13,21,50], although others found no significant effect of these factors [35,51,52]. Using age corrected or education level corrected scoring guide would be desirable in future studies of cognition in ALS.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Not only has the ECAS shown high sensitivity and specificity to cognitive impairment against a full neuropsychological battery (17)(18)(19)(20)(21), it has high clinical utility in describing the nature of these impairments. Monitoring progression of cognitive and behavioural symptoms may have important implications for patient management, treatment, prognosis, end-oflife decision making, and caregiver burden (22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The ECAS is a short screening tool designed with high clinical utility and is administrable by non-neuropsychological health care professionals. It has been validated against a comprehensive neuropsychological battery in Scottish (17), German/Swiss-German (15,18), Italian (19), Chinese (20), and Irish populations (21).…”
Section: Introductionmentioning
confidence: 99%